Pengaruh Iklim Organisasi dan Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru di SMP Negeri 22 Kota Jambi Jambi: Pengaruh Iklim Organisasi dan Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru di SMP Negeri 22 Kota Jambi - Afrida, Veni (Indonesian Educational Administration and Leadership Journal (IDEAL), 2023)
This study aims to determine the effect of organizational climate and principal leadership together on teacher performance. This study uses quantitative research methods with survey research design. The population in this study were teachers at SMP Negeri 22 Jambi City. The sampling technique in this study was to use total sampling, with a sample size of 42 teachers. The data analysis technique used in this research is descriptive analysis technique processed with the help of SPSS 23.0 for windows application. The results in this study are: 1) There is an influence of organizational climate on teacher performance. 2) There is an influence of principal leadership on teacher performance. 3) There is an effect of organizational climate and principal leadership together on teacher performance. It is concluded that these two variables have an influence on teacher performance, so it needs to be considered to maximize teacher performance. Â Keywords: Organization, Leadership, Performance, Teachers